Frailty transitions and associated clinical outcomes in patients with stable COPD: A longitudinal study - Bernabeu-Mora, Roberto (PLoS One, 2020)
BACKGROUND: Although frailty is a frequent occurrence in chronic obstructive pulmonary disease (COPD) patients, evidence on the frequency of frailty transition is scarce. AIMS: The present study aimed to describe the frailty status transition rates over a 2-year period and their associated clinical outcomes in stable COPD patients, and to determine predictors of improvement in frailty status. METHODS: We prospectively included 119 patients with stable COPD (mean age ± SD, 66.9 ± 7.9 years) over a follow-up period of 2 years. Frailty was assessed using the Fried criteria (unintentional weight loss, weakness, exhaustion, low activity level, and slow walking speed). Several demographic, clinical, and health-related variables were measured. We calculated the rates for each of the frailty transitions (no change, improvement, or worsening) between baseline and 2 years. Outcomes were compared using one-way analysis of variance and predictors of improvement were identified in multivariate logistic regression. RESULTS: After 2 years of follow-up, 21 (17.6%) patients had an improved frailty status, 14 (11.7%) had worsened, and 84 (70.5%) had maintained the same frailty status. The worsening group (vs no change group) had greater dyspnea (p = 0.013) and disability (p = 0.036) and lower handgrip strength (p = 0.001). In contrast, the improved group (vs no change group) had greater handgrip (p<0.001) and quadriceps strength (p = 0.032). Furthermore, the improved group had greater handgrip strength (p<0.001), quadriceps strength (p = 0.003), physical activity (p = 0.008), and lower disability (p = 0.019) than the worsening group. Additionally, we determined that the 5STS test (≤ 13.6s) and exacerbations (≥ 2) were independent predictors for improvement in frailty status [adjusted OR 9.46, p = 0.058 and adjusted OR 0.12, p = 0.026, respectively]. CONCLUSIONS: Frailty is a dynamic process for approximately one-third of patients with stable COPD and transitions in frailty status are associated with significant changes in clinical outcomes. The 5STS and exacerbations were independent predictors of improvement in frailty status.